Fluorescence spectroscopy for monitoring reduction of natural organic matter and halogenated furanone precursors by biofiltration. (June 2016) - Peleato, Nicolás M.; McKie, Michael; Taylor-Edmonds, Lizbeth; Andrews, Susan A.; Legge, Raymond L.; Andrews, Robert C.
Abstract: The application of fluorescence spectroscopy to monitor natural organic matter (NOM) reduction as a function of biofiltration performance was investigated. This study was conducted at pilot-scale where a conventional media filter was compared to six biofilters employing varying enhancement strategies. Overall reductions of NOM were identified by measuring dissolved organic carbon (DOC), and UV absorbance at 254 nm, as well as characterization of organic sub-fractions by liquid chromatography–organic carbon detection (LC-OCD) and parallel factors analysis (PARAFAC) of fluorescence excitation-emission matrices (FEEM). The biofilter using granular activated carbon media, with exhausted absorptive capacity, was found to provide the highest removal of all identified PARAFAC components. A microbial or processed humic-like component was found to be most amenable to biodegradation by biofilters and removal by conventional treatment. One refractory humic-like component, detectable only by FEEM-PARAFAC, was not well removed by biofiltration or conventional treatment. All biofilters removed protein-like material to a high degree relative to conventional treatment. The formation potential of two halogenated furanones, 3-chloro-4(dichloromethyl)-2(5H)-furanone (MX) and mucochloric acid (MCA), as well as overall treated water genotoxicity are also reported. Using the organic characterization results possible halogenated furanone and genotoxicity precursors are identified. Comparison of FEEM-PARAFAC and LC-OCD results revealed polysaccharides as potential MX/MCA precursors. Highlights: Unique removal performance of several fluorescence components by biofiltration. A humic-like component recalcitrant to biofiltration was identified. Granular activated carbon as a biofilter support media increased organic reduction. Halogenated furanone and genotoxicity was correlated to organic components. Results suggest polysaccharides as a possible halogenated furanone precursor.